Pelatihan Pijat Bayi Di Masa Pandemi Covid-19 - Sri Dinengsih; Eka Oktavia (J.Abdimas: Community Health, 2023)
Disturbances or difficulties will usually interfere with the ideal growth and development of the baby. Disrupted growth and development disorders will occur if there are genetic or environmental factors that do not meet the basic needs of growth and development. One of the growth and development disorders in infants is weight gain and sleep patterns that are not sound. effort to optimize growth and development during the golden period in infants and is to provide good encouragement or stimulation to children. Parents can provide good encouragement or stimulation to children such as tactile stimulation in the form of baby massage. Community service aims to increase knowledge about the practice of infant massage. The subject of this activity is mothers who have babies and toddlers. This activity uses online/online/zoom media. carried out on Saturday, August 14 2022 via online/zoom media, the target target is mothers who have babies and toddlers as many as 15 mothers in Rt 13 Rw 13 Pisangan Timur Village, East Jakarta. The method consists of 3 stages: initial survey, implementation, evaluation. The results of the initial survey were mothers with poor knowledge of 33%, the implementation used the question-and-answer lecture method and demonstrations. The final evaluation is that the mother can practice massage on her baby and the mother has 100% good knowledge. It is hoped that this community service can provide insight to mothers about infant massage and be able to apply infant massage practices.